Zondervan handbook of biblical archaeology - Price, Randall, 1951-; House, H. Wayne (Grand Rapids, MI, Zondervan Academic, 2017)
The Zondervan Handbook of Biblical Archaeology is a reference resource for anyone interested in archaeology and its relevance to biblical, theological, and apologetic studies. Illustrated with full-color photos, charts, and maps, this handbook provides readers with a wealth of information that complements and supplements the historical context of the Bible. The Zondervan Handbook of Biblical Archaeology includes an introduction to the field of archaeology for readers who might not be familiar with the methods, practices, and importance of this area of study. Included in this section is an annotated bibliography of important biblical archaeological reports, books, and journal articles for further study. The rest of the handbook is devoted to a book-by-book (Genesis through Revelation) presentation of the most significant archaeological discoveries that enhance our understanding of the biblical text, including a section on the intertestamental period. A rich array of visual images including photos of excavations sites, coins, maps, artifacts, and historic structures allows readers to immerse themselves in the world of the Bible. This monumental work gives readers the opportunity to visit ancient sites and historical places while remaining in the comfort of their own home. - Publisher
Introduction to biblical archaeology -- Archaeology and the Old Testament. Introduction to archaeology and the Old Testament -- The Pentateuch -- The historical books -- Wisdom literature -- The prophets -- Archaeological discoveries and the Old Testament ; Archaeology and the intertestamental period. Introduction to the intertestamental period -- The Second (Zerubbabel) Temple -- The Second (Herodian) Temple -- The Dead Sea Scrolls ; Archaeology and the New Testament. Introduction to archaeology and the New Testament -- The Gospels and Acts -- The letters of Paul -- The General Letters and Revelation -- Archaeological discoveries and the New Testament
"A book by book guide to archaeological discoveries related to the Bible"--cover
Includes bibliographical references (pages 379-394) and index
Keywords: Bible -- Antiquities; Bible -- Evidences, authority, etc